Antifouling Surfaces and Materials From Land to Marine Environment - Zhou, Feng (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book reviews the development of antifouling surfaces and materials for both land and marine environments, with an emphasis on marine antibiofouling. It explains the differences and intrinsic relationship between antifouling in land and marine environments, which are based on superhydrophobicity and superhydrophilicity respectively. It covers various topics including biomimetic antifouling and self-cleaning surfaces, grafted polymer brushes and micro/nanostructure surfaces with antifouling properties, as well as marine antibiofouling. Marine antibiofouling includes both historical biocidal compounds (tributyltin, copper and zinc) and current green, non-toxic antifouling strategies. This book is intended for those readers who are interested in grasping the fundamentals and applications of antifouling. Feng Zhou is a professor at the State Key Laboratory of Solid Lubrication, Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences.